1998
DOI: 10.2169/internalmedicine.37.265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations due to a Point Mutation of the Mitochondrial tRNAleu(UUR) Ge Five Families with Diabetes Mellitus.

Abstract: It has been shown that an adenine (A) to guanine (G) transition at position 3243 of the mitochondrial transfer RNA(tRNA)leu(UUR) gene is associated with a subgroup of diabetes mellitus. Therefore, we screened for this transition in 86 patients with non-insulin-dependent diabetes mellitus (NIDDM)in which two or three generations were affected with diabetes, in 14 patients with insulin-dependent diabetes mellitus, and in 9 families with diabetes mellitus and/or associated disorders suggesting mitochondrial gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Delayed-onset steroid-unresponsive NS with focal segmental glomerulosclerosis, mostly ascribed to the 3243 MELAS mutation, has been reported in children and adults, in association with muscle weakness, neurological disturbance, deafness, pigmentary retinopathy, and/or diabetes mellitus [9,10,11,12,13,14,15]. Proteinuria was the first symptom of the disease in 12 patients aged 10-32 years [16,17,18,19,20,21]. There have been rare reports of NS linked to RC disorders in the absence of the MELAS mutation; one was associated with quinone deficiency [9,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed-onset steroid-unresponsive NS with focal segmental glomerulosclerosis, mostly ascribed to the 3243 MELAS mutation, has been reported in children and adults, in association with muscle weakness, neurological disturbance, deafness, pigmentary retinopathy, and/or diabetes mellitus [9,10,11,12,13,14,15]. Proteinuria was the first symptom of the disease in 12 patients aged 10-32 years [16,17,18,19,20,21]. There have been rare reports of NS linked to RC disorders in the absence of the MELAS mutation; one was associated with quinone deficiency [9,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Delayed-onset NS has occasionally been the first manifestation of the disease and the 3243 MELAS mitochondrial (mt) DNA mutation has been detected in most cases [1,16,17,18,19,20,21]. To date, however, respiratory chain (RC) deficiency has never been described as a cause for congenital NS, although secondary mitochondrial dysfunction has been documented in NS of Finnish type.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features were variable amongst subjects carrying mitochondrial mutations. Although defective pancreatic β‐cell function has been demonstrated in diabetic patients carrying this mutation (Kadowaki et al ., 1994; Velho et al ., 1996; Shigemoto et al ., 1998), the mutation carriers in this study showed variable fasting plasma C‐peptide levels (0.23–0.83 nmol/l). Only one subject required insulin treatment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The parathyroid gland may also be vulnerable to mutations in mtDNA because its function requires a high energy supply. In fact, idiopathic hypoparathyroidism has been described in another mitochondrial encephalomyopathy, Kearns-Sayre syndrome (14)(15)(16)(17), as well as in diabetic patients with an A3243G mutation of mtDNA (18,19 may also be necessary to examine mutations in the mtDNAof individuals with idiopathic hypoparathyroidism, especially those with a family history of the disease and/or with diabetes mellitus or impaired hearing.…”
Section: Discussionmentioning
confidence: 99%